Seven samurai [videorecording (DVD)] - Kurosawa, Akira, 1910-1998; Mifune, Toshiro, 1920-1997; Shimura, Takashi, 1905-1982; Tsushima, Keiko, 1926-2012; Shimazaki, Yukiko, 1931-; Chiaki, Minoru, 1917-1999; Ōshima, Nagisa, 1932-2013 (Criterion collection, 2006)
Tells the story of a sixteenth-century village whose desperate inhabitants hire seven out-of-work warriors to protect them from invading bandits.